Devoir de mémoire et droit à l’oubli vs. devoir d’oubli et droit de mémoire - Sylvie Anne Goldberg (E-Spania)
The play between memory and oblivion is an argumentative figure which human thought has made great use of in the past. The techniques of collecting, storing and processing information that have developed over the past quarter century give these games a concrete character, by showing how our memories and omissions can be infinitely arranged and reconfigured or how genetic traces make it possible to review certain elements of historiography. This article analyses the resistance that these advances raise, such as the resistance to claiming a right to oblivion or the resistance that Yerushalmi called the “terror of oblivion,” i.e. the concern about the emergence of new forms of totalitarianism, unique thinking or collective manipulation of our beings and minds.